Al-Farabi's Socio-Political Philosophy and Implementation Towards Democracy - Agustina, Agustina; Mutiullah, Mutiullah (Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
From Greece to the contemporary era, democracy has become the main pillar of the global political system with its basic principle that power comes from the people, making democracy an ideal paradigm. As is well known, there is an impression that democracy has regressed. There are even claims that democracy is an illusion. This article aims to explain how Al-Farabi's socio-political philosophy can be integrated and applied concretely in the dynamics of democracy. The research approach uses qualitative theoretical analysis by referring to Al-Farabi's major works, especially